Self-regulated learning with mobile devices for university students: exploring the impacts on academic vocabulary development - Tahereh Boroughani; Ismail Xodabande; Sedigheh Karimpour (Springer, 2023)
Abstract The present study explored the impact of mobile-assisted self-regulated learning (SRL) on developing university students' knowledge of academic vocabulary in English. The participants were 49 students in experimental (N = 28) and control (N = 21) learning conditions. Those in the experimental group studied 70 academic words using digital flashcards application installed on their mobile devices (i.e., smartphones), and the control group learned the same words using traditional materials (i.e., word lists). The participants' vocabulary knowledge was tested before and after the treatment, and their test scores were analyzed using mixed between-within-subjects analysis of variance (ANOVA). The findings indicated a significant main effect for time in both SRL interventions, as both strategies were effective in scaffolding university students' academic vocabulary development, and the learning gains were significant in post- and delayed post-tests. Additionally, the findings revealed a significant main effect for mobile-assisted SRL in that participants in the experimental group outperformed those in the control group on post-treatment tests. Accordingly, the results provide empirical evidence for the effectiveness of mobile-assisted vocabulary learning in the SRL mode. The study offers implications for addressing the academic vocabulary learning needs of English as a Foreign Language (EFL) university students.